Molecular phylogeny of Artemisia (Asteraceae-Anthemideae) with emphasis on undescribed taxa from Gilgit-Baltistan (Pakistan) based on nrDNA (ITS and ETS) and cpDNA (psbA-trnH) sequences - Adil Hussain; Daniel Potter; Sangtae Kim; Muhammad Hayat; Syed Bokhari (Plant Ecology and Evolution, 2019)
Background – Gilgit-Baltistan, the Northeast region of Pakistan, is well known for its floristic diversity, including members of the genus Artemisia. Artemisia is a large, taxonomically complex genus including ~500 species of both herbs and shrubs. This study was conducted to determine the phylogenetic position of ten undescribed Artemisia taxa from northern Pakistan, using nrDNA internal transcribed spacer (ITS), external transcribed spacer (ETS) and cpDNA intergenic spacer (psbA-trnH) regions.Methods – The phylogenetic relationships of 28 taxa of Artemisia using separate and combined data sets of sequences of three markers (ITS, ETS and psbA-trnH) were analysed with maximum parsimony, maximum likelihood, and Bayesian approaches. Key results – The results resolve northeastern Pakistani Artemisia, which represent five morphologically defined subgenera, into ten major clades. Subgenera Artemisia and Absinthium are shown to be polyphyletic, while Dracunculus, Pacifica and Tridentatae appear monophyletic. All species of subgenus Seriphidium are retrieved in a single clade that also includes annual species from subgenus Artemisia. In the Flora of Pakistan, Seriphidium is described as a separate genus but in this study, Seriphidium fell within the genus Artemisia. In addition, on the basis of phylogenetic analysis, we present evidence that ten as-yet undescribed taxa are present in northeastern Pakistan based on newly recognized three groups (Groups I, II and III) of taxa within the genus Artemisia. One undescribed taxon from group I was placed within the subgenus Dracunculus clade and the remaining nine taxa from groups II and III were placed in the subgenus Absinthium clade. Morphological studies coupled with modern molecular techniques may lead to a new infrageneric classification of the genus Artemisia. It will also clarify and characterize the undescribed taxa reported in this study.